2020
DOI: 10.1530/rep-17-0789
|View full text |Cite
|
Sign up to set email alerts
|

Murine germ cell-specific disruption of Ift172 causes defects in spermiogenesis and male fertility

Abstract: Intraflagellar transport (IFT) is a conserved mechanism essential for the assembly and maintenance of most eukaryotic cilia and flagella. IFT172 is a component of the IFT complex. Global disruption of mouse Ift172 gene caused typical phenotypes of ciliopathy. Mouse Ift172 gene appears to translate two major proteins; the full-length protein is highly expressed in the tissues enriched in cilia and the smaller 130 kDa one is only abundant in the testis. In male germ cells, IFT172 is highly expressed in the manch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 58 publications
2
14
0
Order By: Relevance
“…Among the downstream mRNAs, several targets were previously demonstrated to be associated with different periods of sperm generation. Zhang et al found that IFT25 and IFT57 were reduced in Ift172 mutant mice, which can affect the structural protein transport during the spermatogenesis phase (Zhang et al., 2020). Moretti et al suggested that TBL1XR1 interacts with SLY, which is closely associated with the master genes of spermatid transcriptional regulation and further modulated the chromatin remodelling process (Moretti et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Among the downstream mRNAs, several targets were previously demonstrated to be associated with different periods of sperm generation. Zhang et al found that IFT25 and IFT57 were reduced in Ift172 mutant mice, which can affect the structural protein transport during the spermatogenesis phase (Zhang et al., 2020). Moretti et al suggested that TBL1XR1 interacts with SLY, which is closely associated with the master genes of spermatid transcriptional regulation and further modulated the chromatin remodelling process (Moretti et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Ift88 -/mice display impaired spermiogenesis with spermatids carrying several anomalies [29]. Other intraflagellar transport genes were similarly selected during evolution [27] and are essential during spermiogenesis, including Ift20 [30], Ift25 [31], Ift27 [32], Ift74 [33], Ift140 [34] and Ift172 [35].…”
Section: Evolution Of Mammalian Spermmentioning
confidence: 99%
“…IFTA interacts with dynein motors and IFTB with kinesin motors to transport proteins along microtubules. IFT transport is essential for mammalian spermiogenesis [29][30][31][32][33][34][35].…”
Section: Intraflagellar Transport (Ift) Proteinsmentioning
confidence: 99%
“…The tissue‐/cell‐specific knockout technique is a game‐changer. Using the Stra8‐cre transgenic mice, we successfully disrupted Ift20, Ift25, Ift27, Ift140, Ift74, Ift81 , and Ift172 (Liu et al, 2017; Qu et al, 2020; Shi et al, 2019; Z. Zhang et al, 2016; Y. Zhang et al, 2017, 2018; S. Zhang et al, 2020) in male germ cells. All these mutant mice were grossly normal, but spermiogenesis and fertility were affected.…”
mentioning
confidence: 99%
“…Each IFT component might be responsible for carrying specific cargo proteins for sperm flagella formation. For example, IFT74 and IFT81 are likely more important for carrying tubulin for the sperm core axoneme structure formation (Shi et al, 2019; S. Zhang et al, 2020). IFT25 and IFT27 are likely uninvolved in core axoneme formation, but they are more likely to carry proteins for assembling sperm accessory structures (Liu et al, 2017; Y. Zhang et al, 2017).…”
mentioning
confidence: 99%